Peningkatan Produktivitas Pemasaran UMKM Kopi Mentari dengan Pendekatan Analisis SWOT dan Marketing Mix - Livia (Universitas Katolik Musi Charitas, 2019)
Mentari Coffee SME’s are one of the SME’s that are engaged in processing coffee beans in Palembang. Based on the results of observations and interviews conducted, it is known that the applied marketing strategy is not optimal, causing low levels of marketing and benefits. The low level of marketing and the profit obtained result in the productivity of the marketing row low. Current marketing productivity is 1,1249. In formulating the right marketing strategy, SWOT analysis is used to identify the strengths, weaknesses, opportunities, and threats faced by SME’s. Then the SWOT matrix is used to produce an improvement strategy, which is then developed using the marketing mix (7P). The implementation of improvements included product aspects (increasing the number of variants and types of products, making product logo stickers, providing varied prices, make the label the date of production, create standard operational production), price aspects provision of prices which vary), place aspect (increasing the number of channel stores), promotion aspects (advertising through Instagram, selling online through shopee), proccess aspect (increasing service facilities), people aspect (adding workers), and physical evidance aspect (provides a comfortable waiting room). Marketing productivity after the improvement implementation was 1.1431. From these data, there is an increase in marketing productivity by 1,82%.